Trajectory and attitude modeling and propagation for reentry debris with fragmentation implementing voxels meshs - Jhonathan Orlando Murcia Piñeros (2018)
Actually, more than 17.000 objects are in orbit around the Earth, with an estimated total mass of 6.500.000 kg. All of them with dimensions superior to 10 cm and some orbiting without control. In other words, they are orbital debris. In orbit, the debris represents a hazard to operational satellites and aerospace operations due to the high probability of collisions. With the exponential increment of space activities and without regulations it is expected a proportional increment in the debris population and an increase the risk for the space activities. Because the interaction of the debris with the atmosphere of the Earth and the solar activity, the debris began to lose energy and decay. During the de-orbit process, the debris fall into the Earths atmosphere at hypersonic speeds and these objects can be break-up and/or fragmented due to the aerodynamics, thermal and structural loads. It is important to obtain the trajectory and attitude of any fragment to determine the possible survival mass, impact area, hazard conditions and risk to the population, the air traffic control, and infrastructure. Different computational tools are used to determine the impact of the debris during reentry. These tools implement different models complemented with data from observations and laboratories. In this case, it is proposed a computational code to integrate the equations of motion and to propagate the dynamics and kinematics of the possible survival fragments. The new model implements the voxel method to determine the aerodynamic conditions and the fragmentation of the body. It is also analyzed the results of trajectories with six degrees of freedom, atmospheric winds, and Magnus effect. The mathematical model and computational code are validated in three degrees of freedom. Results are compared with data from other computational tools available in the scientific literature. The results show a good approximation with the report cases of study. New results are generated in the simulations of rotational bodies, due to the influence of aerodynamic forces in the trajectory and the changes in the stagnation regions. Because the implementation of wind and rotation of the debris, the fragments increased the survivability and the dispersion area. These information confirm the initial hypothesis and increases the applications of the actual tool in future reentry predictions.